Uses and images of time in students of secondary school: between school, family and community - M Carmen Moran; Lucia Iglesias; German Vargas; Javier Francisco Rouco (Sociedad Iberoamericana de Pedagogía Social, 2012)
The article focuses on the analysis of school time and its relation with the vital family and community experience of Spanish compulsory secondary education (ESO) students. The results make it possible to understand ideas such as the conditioning nature of school times on teenagers socializing development and opportunities, the interconnection between the types of school time management and family and community experience, the uneven vision and, even in some cases contradictory, on the uses and images of school and social time among students and secondary school teachers, the opening to the social environment of centers as infrastructures offering their facilities to be used for other non-teaching activities and the confirmation of new technologies as important agents of socialization. A better understanding of the interdependence between teenage school time socialization processes allows the formulation of new questions and broadens the social, political and academic debate about ways of management for personal, educational and social times